Swarm and ESR observations of the ionospheric response to a field‐aligned current system in the high‐latitude midnight sector. Issue 11 (10th June 2015) - Pitout, F.; Marchaudon, A.; Blelly, P.‐L.; Bai, X.; Forme, F.; Buchert, S. C.; Lorentzen, D. A.
Abstract: We present a conjunction between the Swarm fleet and the European Incoherent Scatter Svalbard Radar (ESR) on 9 January 2014. The Swarm orbit in the early phase of the mission gives us the unique opportunity of sequencing the temporal evolution of the observed field‐aligned current system in the nightside, near magnetic local midnight. These field‐aligned currents are seen to move poleward through the radar field of view and to affect the observed ionosphere. The upward field‐aligned current (FAC) is responsible, at least in part, for the heating of the ionospheric electrons. It is less clear whether the downward FAC cools the ionosphere. We use the TRANSCAR model of the ionosphere to quantify the thermoelectric effect that comes into play. Finally, we compare the plasma parameters measured by the Langmuir probe on board Swarm and the ESR and conclude on an agreement within the errors. Key Points: Conjunction between Swarm and the EISCAT Svalbard Radar The thermodynamics of the ionosphere in response of FAC is observed and modeled Cross calibration of the LP on Swarm C and the ESR shows good agreement